PENGARUH SISTEM INFORMASI AKUNTANSI BERSTANDAR SAK ETAP PADA KOPERASI SIMPAN PINJAM DI KECAMATAN GADING CEMPAKA KOTA BENGKULU - Anisa Ade Oktari; Elviza Diana (Universitas Prof.Hazairin,SH Bengkulu, 2019)
The role of cooperatives is still very important for the local community. One type of cooperative that helps the household economy is a savings and loan cooperative. This cooperative gives credit to all people who fulfill the requirements as members of cooperatives and those who share economic interests. This savings and loan cooperative is said to be good if the accounting information system (SIA) is in accordance with the SAK ETAP standard as a benchmark in decision making. SIA consists of three subsystems, namely: transaction processing system, financial reporting system, management reporting system. This study uses quantitative methods with primary data sources in the form of questionnaires. The population of this study is a savings and loan cooperative in the ivory cemapaka sub-district of Bengkulu City. The sample used is 50 employees. The results of this study partially show that there is a significant influence on the transaction processing system towards SAK ETAP, there is a significant influence on the financial reporting system towards SAK ETAP, there is a significant influence on the management reporting system towards SAK ETAP, and simultaneously shows that SIA as a whole has an effect significant to SAK ETAP. The results of this study can be suggested that savings and loan cooperatives in Ivory Cempaka sub-district update accounting software for those who already use computerization, while those who are still manual can immediately switch to computers in inputting accounting data to make it more practical and shorten time.